National Health Service : deputation to Minister of Health on 17 June 1946 (report) - Bevan, Aneurin, 1897-1960
1946-06-25 1946 1940s 9 pages -5- for everybody to get exactly what they wanted, then he felt that there should be provision for privacy if people wanted it, at an extra charge. They did not want to encourage the growth of nursing homes and were anxious to keep all the specialists attached to the hospitals. If nursing homes were allowed to develop then they would be staffed with personnel badly needed in hospitals. A dual system would thus soon develop. It was therefore advisable that there should be a carry-over period during which there could be private beds attached to hospitals for the use of specialists who wanted to give private treatment. The language of the Bill did, however, insist that the first claim on privacy should be the patient who needed the bed on medical grounds. An important factor in this connection was that the hospitals of the future would not be dependent on funds from private sources. Preventive Health Services The most important of the preventive health services was good housing. That of course was not part of the Health Service Bill but nevertheless the Government were getting ahead with it fairly well. He was hoping that they would be able to build in the course of the present Parliament enough houses to give everybody a separate dwelling, after which slum clearance would be dealt with. A second factor of the preventive health service was water supply, especially in rural districts where the situation was lamentable. Water service schemes were coming in day after day, the only limitation being labour and materials. There would be a revolution in pipe water supplies in future. Thirdly, there was nutrition. Doctors would all agree that nutrition was the most important health service. This was being dealt with by means of children's allowances, free milk and meals in school, and distribution of cod liver oil and orange juice. He was opposed to including preventive health services in the Bill; but these services were developing and would continue to do so, more than in any other country in the world. Research was developing into the common cold though not much headway had been achieved. Rheumatism was one of the most neglected complaints. The Canadian Hospital at Cliveden had been given to the Government and research into rheumatic fever in children and into rheumatism generally, would be conducted there. The doctors there would be given grants and apparatus and there would be no limit to the Government's powers of research. Medical Education All the medical schools would be full during the present year, and there would be more applicants than facilities. One of the by-products of the new scheme would be that the Minister would be able to create teaching schools. In the past they had grown up and had been dependent upon heavy grants and donations from rich persons, usually by way of diverting it from the Chancellor of the Exchequer. In future the Minister of Health would be able to create a hospital as a teaching hospital and add to the teaching facilities. The health services of the country could not be staffed with good doctors unless the country was able to tap income levels not at present tapped. Too many doctors were recruited from classes of the population who were able to afford the training, rather than from those with a vocation for medicine. If the wider area among the working classes was to be tapped, then there would have to be much more generous 292/847/4/113